Towards an EU Action Plan on Cetacean Bycatch. (October 2016) - Dolman, Sarah; Baulch, Sarah; Evans, Peter G.H.; Read, Fiona; Ritter, Fabian
Abstract: For decades, cetacean bycatch has been a major conservation and welfare concern in Europe, with high numbers of harbour porpoises, dolphins and whales continuing to die each year. Despite binding legal requirements to reduce bycatch, there has been limited effective monitoring or mitigation. Bycatch is also an important welfare issue. At this critical juncture, with discussion of incorporating monitoring and mitigation of bycatch of protected species in Europe into the Data Collection Framework and Technical Measures Framework taking place to help deliver the reformed Common Fisheries Policy (CFP), a clear, effective strategy could identify the steps that are required by all EU Member States to reduce bycatch towards zero. Here, implementation of current monitoring and mitigation obligations are reviewed. Recommendations are made for the provision of clear EU guidance in order to improve and unify population surveillance and bycatch monitoring, with enhanced implementation and enforcement from Member States. A more regionalised evidence-based approach to monitoring and mitigation is in line with the move to more regionalised management under the CFP, with Member States robustly showing that bycatch levels are decreasing over a set period of time (e.g. 5 years) by a specified amount. To this end, an EU Action Plan on Cetacean Bycatch, comparable to the existing 2012 Action Plan for reducing incidental catches of seabirds in fishing gear, might be beneficial and could ultimately form a model for an international Food and Agricultural Organisation (FAO) Cetacean Bycatch Reduction Action Plan. Highlights: Cetacean bycatch in Europe is a major conservation and welfare concern. Despite decades of relevant law, there has been limited effective monitoring or mitigation. Several thousand harbour porpoise die annually in nets in European waters. Bycatch mitigation should be applied to the zone between zero bycatch and any threshold used to deliver the zero bycatch aim. Recommendations are made on ways to robustly improve collection of data and mitigation to reduce bycatch towards zero. Filling existing data gaps and implementing bycatch mitigation concurrently would fulfil existing legislative requirements. Development of an EU Action Plan on Cetacean Bycatch and the establishment of Regional Bycatch Reduction Teams are recommended.